Spatio-temporal variation of PM2.5 pollution in Xinjiang and its causes: The growing importance in air pollution situation in China - Yao, Xuefeng; Ge, Baozhu; Li, Aibing; Chen, Guanjun; Fan, Fan; Xu, Danhui; Wang, Yuge; Tang, Xiao; Kong, Lei; Wang, Zifa (Frontiers in Environmental Science, 2023)
Due to the differences in topographic features, water vapor distribution and emission structures between the north and south of Xinjiang Uygur Autonomous Region (hereinafter Xinjiang), the air pollution exhibits remarkable spatial heterogeneity in this region. In this study, Xinjiang is divided into four regions from north to south at the municipality scale based on the data from air quality monitoring sites recorded from 2013–2019, namely, the clean area in the north of northern Xinjiang (region I), the heavily polluted area of the Urumqi-Changji-Shihezi region (region Ⅲ), the moderately polluted area in the north of southern Xinjiang (region Ⅱ), and the severely polluted area in the south of southern Xinjiang (region Ⅳ). For highly polluted regions in northern and southern Xinjiang, regions Ⅲ and Ⅳ are compared with those typical polluted regions in central and eastern China, and the spatio-temporal variation characteristics and the causes of PM2.5 pollution in each sub-region are discussed. The results show that the region Ⅲ is a typical area with anthropogenic air pollution source, where the occurrence frequency of PM2.5 pollution with the intensity of moderate level or above (18%) is higher than the most heavily polluted area in central and eastern China (16%, regions from the south of North China to the west of Huang-Huai). The region IV is a typical area affected by dust weather, where the pollution frequency being about 52% is much higher than that in other typical polluted regions. In addition, under the combined effects of anthropogenic sources and dust aerosols, the pollution duration in region II is prolonged. Therefore, in contrast to the remarkable improvement of air quality in central and eastern China, the air pollution in typical regions of Xinjiang has become relatively more severe in recent years. Moreover, as Xinjiang is in the upstream of the central and eastern China in the mid-latitude westerlies, the heavy pollution due to sand and dust, anthropogenic sources and their mixing effects has a far-reaching impact on the downstream areas, further highlighting the growing importance of pollution prevention and control in Xinjiang.